Engineering design process-based computational thinking abilities among brilliant and talented students - Seyit Sonay; Ceylan Kiray (International Journal of Advanced Science and Computer Applications, 2022)
Computational thinking abilities employed by gifted and talented students in integrated STEM activities based on the EDP are the focus of this investigation. The study makes use of a qualitative research strategy known as the case study design. Students from the Science and Arts Center are among the participants. Based on the EDP, integrated STEM activities were undertaken for 10 weeks and included Lego set-based robotics and 3D modeling exercises. To obtain data, the study relied on the STEM activity booklet, researchers' field notes, and video recordings of instructional processes. Content analysis was used to examine the data that had been gathered. Participating in integrated STEM activities that are based on the EDP, gifted and talented students demonstrate active use of critical thinking skills while providing explanations, making associations, questioning information and giving justifications, solving problems, thinking creatively and making generalizations, and attempting to persuade others. An important contribution to the growing body of knowledge on how gifted and talented kids' computational thinking abilities are enhanced by robotics and 3D robot modeling is supplied by this research.